Harmonization of Child-Friendly City Regulation at the Local Level - Pratiwi, Dian Kus; Muhammad Addi Fauzani; Aprillia Wahyuningsih (Universitas Islam Negeri Raden Intan Lampung, 2026)
The fulfillment of Child-Friendly City (CFC/KLA) policies represents both a constitutional obligation and an international commitment within the framework of children’s rights governance. Nevertheless, the implementation of KLA policies in several regions of Indonesia remains suboptimal, partly due to the lack of vertical harmonization between local regulations and national regulatory frameworks concerning Child-Friendly Cities. In this regard, local governments hold a strategic role in implementing child protection policies at the regional level. This study aims to analyze, first, the legal policy strategies adopted by the Local Governments of Yogyakarta City, Sleman Regency, and Bantul Regency to achieve KLA status; and second, the vertical harmonization of local regulations with higher regulations. This research employs normative legal research, drawing on statutory and conceptual approaches. The findings show that each local government adopts different legal policy strategies based on institutional capacities, socio-legal conditions, and regional policy priorities. The study also identifies that several local regulations have not been fully harmonized with Presidential Regulation Number 25 of 2021 concerning Child-Friendly City Policy and Minister of Women’s Empowerment and Child Protection Regulation Number 12 of 2022 concerning the Implementation of Child-Friendly Cities. The inconsistencies are reflected in differences in KLA assessment indicators, the legal form of Regional Action Plans (RAD KLA), implementation stages, and the composition of KLA Task Forces. These findings indicate fragmented local regulatory governance and the absence of a uniform harmonization model for implementing Child-Friendly City policies at the local level.